(untitled) (Contemporary Journal of Social Science Review, 2025)
The research described in this paper is a systematic literature review on the topic of sustainable value creation enabled by Sustainable Development Goals (SDGs) reporting examined through the prism of both economics and accounting. As the need and urgency of businesses to report in line with global sustainability frameworks continue to grow, the SDG reporting has become one of the major tools of reporting corporate contributions to sustainable development. There have however been doubts as to the extent of integration of such reporting into economic decision-making and accounting. The present study is a synthesis of peer-reviewed publications between 2015 and 2023 that allows assessing the level of current knowledge, methodologies, and frameworks to measure and report corporate SDG performance. The review is supported by the systematic approach based on Tranfield et al. (2003) with the clear screening, coding, and content analysis procedures. A total of 32 scholarly articles were identified due to their relevance, originality and rigor in their choice of methods. Findings indicate four key learnings: (1) SDG reporting is not yet strategically integrated in financial planning and decision-making processes; (2) the monetization of SDG impacts with the help of economic tools (Social Return on Investment, SROI, and Cost-Benefit Analysis, CBA) is not used consistently and effectively; (3) conventional accounting systems are ill-suited to measure non-financial and sustainability-focused performance; and (4) a lack of fragmentation in reporting standards undermines cross-comparability and benchmarking. The results point to the great difficulty in moving the story of sustainability into quantitative and like-comparable indicators of value. This paper suggests further SDG embedding in the financial accounting process, the creation of uniform impact valuation models, and more coordination of reporting standards. It ends with drawing major limitations and suggesting the ways of future research, such as the construction of hybrid value models, long-term impact measurement, or the use of digital technologies in SDG reporting and assurance.